The influence of diversity on boards on profitability: an overview across Iberian listed companies - Lopes, I. T.; Ferraz, D. P.; Martins, M. M. (Corporate Ownership And Control, 2016)
In modern economies, the corporate governance principles have been understood as drivers that mitigate the risk derived from the existing gap between managerial practices and ownership structure. This research contributes to the literature review, analyzing the relationship between the board characteristics, audit firms, and a set of indicators taken as proxies of performance. Based on a dataset of 124 non-financial companies, a linear model was regressed. We found that some characteristics of board of directors significantly influence the companies’ performance. These new insights can also provide new guidelines for policy makers towards the establishment of new common rules and principles that accurately grant the efficiency of corporate governance mechanisms and ensure the desired international comparability. © 2016, Virtus Interpress. All rights reserved.